Tantangan dan Peluang Pewarta Foto Di Era Media Baru - Tripa Ramadhan; Fitria Ayuningtyas; Munadhil Abdul Muqsith (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
Developments in technology and the internet have had a major influence on the journalism industry, including journalistic photography by photo journalists. Technological developments are not only in photography technology but also in the medium of publication. The rapid digitalization and development of social media gave rise to the term "everyone can take pictures". This then triggers its own challenges and opportunities for photojournalists. The purpose of this study is to explain the phenomena that occur as well as describe the challenges and opportunities for photojournalists in the new media era. This study uses a qualitative method with a phenomenological approach. Data collection was carried out by means of observation and interviews, as well as other supporting documents. The result of this research is that challenges come no longer only from fellow professions but more broadly, namely the audience. Photojournalists must be able to adapt to technological developments in order to maintain their existence. The presence of new media also brings benefits for photojournalists to be able to develop themselves as well as their photographic works.Keywords: Photojournalist; Journalistic Photography; New Media; Digitization Abstract Perkembangan teknologi dan internet telah membawa pengaruh besar pada industri jurnalistik, tidak terkecuali fotografi  jurnalistik yang dilakukan pewarta foto. Perkembangan teknologi itu bukan hanya pada teknologi fotografinya tapi juga medium publikasinya. Pesatnya digitalisasi dan perkembangan media sosial memunculkan istilah semua orang bisa memotret. Hal ini lantas memicu tantangan dan peluang tersendiri bagi pewarta foto. Tujuan penelitian ini adalah untuk menjelaskan fenomena yang terjadi juga menggambarkan terkait tantangan dan peluang bagi pewarta foto di era media baru. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Pengumpulan data dilakukan dengan cara obervasi dan wawancara, serta dokumen pendukung lainnya. Hasil penelitian ini adalah tantangan datang bukan lagi hanya dari sesama profesi tapi lebih luas yakni khalayak. Pewarta foto harus mampu adaptasi dengan perkembangan teknologi untuk tetap mempertahankan eksistensinya. Media baru hadir juga membawa manfaat bagi pewarta foto untuk bisa mengembangkan diri juga karya fotonya.Keywords: Pewarta Foto; Fotografi Jurnalistik; Media Baru; Digitalisasi